Pengaruh Intensitas Penggunaan Media Sosial terhadap Konstruksi Pengetahuan Siswa di Era Digital - Leni Misdiyanti; Fitriyanti; Yelna Septiana (PAI RAFAH, 2025)
The utilization of social media as a communication tool and information source among vocational high school students in the digital era presents substantial opportunities for knowledge construction. However, high-intensity social media use also introduces challenges such as distraction, decreased focus, and the risk of spreading invalid information. This study aims to analyze the impact of social media usage intensity on students’ knowledge construction and to identify the challenges and benefits in the context of vocational agricultural education. A quantitative method with structured interviews was employed to explore students’ experiences. The results indicate that with adequate teacher supervision and digital literacy, social media can be optimized as a valid, interactive, and productive learning resource. Therefore, strategies such as curricular integration, digital literacy education, AI technology utilization, social norm implementation, and collaboration among schools, teachers, students, and parents are needed to create a more effective and sustainable digital learning ecosystem